Daily field checking list by Walter Rosene, May 21, 1939 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed at Dunbar Slough, Raccoon River and Ledges State Park by Walter Rosene, Robert Walker, Samuel J. Hyde and Earl Peterson, May 21, 1939. Also notes Ledges State Park had the most shore birds he has seen including 100 Red-backed Sandpipers (Dunlin's). Plustek--flatbed